THE COMPARATIVE STUDY BETWEEN CHATGPT AND QUILLBOT AS AI ASSISTING TOWARD ENGLISH FOREIGN LEANER AT STUDENTS’ UNIVERSITY IN WRITING SKILL - Azzahra, Syeha Nabila; Heryatun, Yayu; Hidayani, Selnistia (Universitas Tanjungpura, 2026)
This study aims to compare two artificial intelligences, ChatGPT and Quillbot, to evaluate their benefits towards EFL learners' Writing skill. English is an international language used for global communication, particularly in contemporary times. Traditional classroom techniques seldom give enough practice, prompting the integration of Artificial Intelligence. ChatGPT utilizes to finding out the topic. Meanwhile, Quillbot utilizes to paraphrase text automatically in sentence or paragraph, and QuillBot will generate several different paraphrasing alternatives, but still retain the original meaning. Moreover, this research employed qualitative descriptive techniques, involving observation and interviews with undergraduate and postgraduate student at the Islamic State University in Banten. Participants engaged in writing using both artificial intelligences to assess their understanding, vocabulary, awareness, grammar, and confidence. The findings reveal that ChatGPT more interactive in finding out the topic but it can be challenging in paraphrasing text. Quillbot, though less in finding out the topic or idea but it has many features to support in writing especially in paraphrasing and summarizing text. The study concludes that both artificial intelligences have unique advantages and disadvantages. Quillbot is more suitable for academic writing or blog articles, because it helps to clear up the sentence structure and ChatGpt is appropriate to find out the idea to begin writing